Synergistic Model of Parent and Teacher Collaboration in Character Education at Islamic Based Schools in Medan City - Pohan, Selamat; Afandi, Ahmad; Waeji, Ibrohem (Fitrah: Journal of Islamic Education, 2025)
Character education is a fundamental aspect in shaping students' personalities, but its effectiveness greatly depends on the synergy between parents and teachers. This study aims to analyze effective synergy models in character education at Al-Ulum Private High School and Jabal Rahmah Mulia Boarding School in Medan. This study uses a qualitative research method with a descriptive approach. Data were collected through in-depth interviews, participatory observation, and document analysis to explore communication patterns, parental involvement, and collaboration challenges. The results show that participatory communication, family support, and a conducive social environment are key factors in successful synergy, which has a positive impact on improving student discipline, responsibility, and honesty. Teachers play the role of murabbi who instill morals, while parents reinforce values at home. The main obstacles include parents' time constraints, differences in perceptions of character education, and the influence of the social environment. This study produced a synergy model based on the Indonesian socio-cultural context that is adaptive to Islamic values and the realities of urban families. The implication is that schools need to strengthen collaboration with parents through digital communication and moral values-based parenting programs to strengthen student character building.